ANALISIS SOSIOLOGI SASTRA NOVEL DR. RATINI KARYA NYOMAN MANDA - Mika, I Wayan (Humanis; Volume 2. No. 3. Maret 2013)
The analysis on the structure and literary sociology  approach in the novel of dr. Ratini, this article aims was to understand the elements of structure and the social aspects that exist in the novel. The theory base have been used in this analysis were the structural theory and the theory of literary sociology. Structural theory have been used based on the Teeuw that were dominant elements in literary work. For the analysis of social aspects were based on the theory presented by Damono and Rene Wellek, the method have been used in this analysis were divided into three phases, that were data collection by the method of reading, data processing and data analysis by analytic descriptive methods, and presentation of the results of the analysis data were by using informal methods.The results have been obtained in this analysis that were revealed of the narrative structure that develop the novel of dr Ratini as follows: incident, plot, setting, characters and characterizations, theme and message. In addition, this analysis also reveals social aspects as follows: aspects of religion (tattwa, moral, ceremony), aspects of romance, magic aspects and technology aspects.
Keywords: Novel, Social, and Romance.